Legal Protection for Carriers of Keris as Cultural Heritage Objects for the Development of Keris Cultural Progress: Analysis of Decision Number 94/pid.sus/2013/PN.Smp - Sjaifurrachman, Sjaifurrachman; Fithry, Abshoril (PT. Riset Press International, 2024)
Sumenep is now beginning to reveal its identity to the people of Indonesia, with its new motto